Derivation of Multipotent Mesenchymal Stromal Cells from Ovine Bone Marrow. (28th February 2018) - Vivas, Daniel; Caminal, Marta; Oliver‐Vila, Irene; Vives, Joaquim
Abstract: In the field of orthopedics, translational research of novel therapeutic approaches involves the use of large animal models (such as sheep, goat, pig, dog, and horse) due to the similarities with humans in weight, size, joint structure, and bone/cartilage healing mechanisms. Particularly in the development of cell‐based therapies, the lack of manageable immunocompromised preclinical large animal models prevents the use of human cells, which makes it necessary to produce equivalent homologous cell types for the study of their pharmacodynamics, pharmacokinetics, and toxicology. The methods described herein allow for the isolation, expansion, manipulation, and characterization of fibroblastic‐like ovine bone marrow–derived multipotent mesenchymal stromal cells (BM‐MSC) that, similar to human BM‐MSC, adhere to standard plastic surfaces; express specific surface markers such as CD44, CD90, CD140a, CD105, and CD166; and display trilineage differentiation potential in vitro. Homogeneous cell cultures result from a 3‐week bioprocess yielding cell densities in the range of 2–4 × 10 4 MSC/cm 2 at passage 2, which corresponds to ∼8 cumulative population doublings. Large quantities of BM‐MSC resulting from following this methodology can be readily used in proof of efficacy and safety studies in the preclinical development stage. © 2018 by John Wiley & Sons, Inc.